Gastrointestinal stromal tumor as cause of acute abdominal pain in a patient with neurofibromatosis type 1: case report and literature review - Blaz-Zavala, Rogelio A.; Villa-Santiago, Hector F.; Flores-García, Alba E.; Diez-Gonzalez, Renata (International Journal of Research in Medical Sciences, 2022)
Acute abdomen is a common and sometimes dramatic clinical condition, which can be fatal if diagnosis is not made in time. There are many etiologies for acute abdominal pain; therefore, the diagnostic approach should be based on clinical assessment, including laboratory and image studies. Neurofibromatosis 1 (NF1) is an autosomal dominant condition, characterized by cutaneous pigmentation and tumor formation along nerves in the brain, skin and other organs, the gastrointestinal stromal tumors are rare mesenchymal neoplasms associated with NF1. The close correlation between both pathologies is well known, and the clinical relevance relies on the different pathogenesis from sporadic gastrointestinal stromal tumor (GIST), with important therapeutic implications as the use of imatinib prior or after surgery, regarding the individual context of the patient. This case report illustrates the management of an NF1 patient presenting with acute abdomen to the emergency room and follow-up.